2015
DOI: 10.1177/1362361315593068
|View full text |Cite
|
Sign up to set email alerts
|

What do the general population know, believe and feel about individuals with autism and schizophrenia: Results from a comparative survey in Denmark

Abstract: Few studies investigate what members of the general population know about individuals with autism. Only one study has previously investigated how beliefs about autism differ from those about other psychiatric disorders. This study surveyed a convenience sample of the general adult population, within the Northern Region of Denmark, about their knowledge, attitudes and beliefs about individuals with autism and schizophrenia. The respondents (N = 440) possessed basic knowledge and were able to differentiate betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 26 publications
8
39
3
Order By: Relevance
“…Myths six and seven relate to the beliefs that people with autism are dangerous or mad. In contrast to our findings, some previous surveys have found low levels of endorsement of the myth that people with autism are dangerous (for example, Durand-Zaleski et al 2012) and show that autism is viewed less negatively than mental health conditions such as schizophrenia (Jensen et al 2015). This inconsistent finding may be a consequence of different methodologies.…”
Section: Discussioncontrasting
confidence: 99%
“…Myths six and seven relate to the beliefs that people with autism are dangerous or mad. In contrast to our findings, some previous surveys have found low levels of endorsement of the myth that people with autism are dangerous (for example, Durand-Zaleski et al 2012) and show that autism is viewed less negatively than mental health conditions such as schizophrenia (Jensen et al 2015). This inconsistent finding may be a consequence of different methodologies.…”
Section: Discussioncontrasting
confidence: 99%
“…Ostensibly, some view people with schizophrenia as being more to blame for their condition, less responsive to treatment, and more helpless. In another survey in which respondents were asked about mental disorders using positive and negative stereotypes, autism was associated with high intelligence and creativity, and schizophrenia was associated with danger [41].…”
Section: Challenges To Making Theater Accessible To People With Asdmentioning
confidence: 99%
“…A number of studies have been conducted on the MHL of schizophrenia (Altweck, Marshall, Ferenczi, & Lefringhausen, 2015;Angermeyer & Matschinger, 2003;Angermeyer, Millier, Rémuzat, Refaï, & Toumi, 2013;A. Furnham & Igboaka, 2007;Jensen et al, 2016;Lauber et al, 2003;Lee & Suh, 2010;Magliano et al, 2001;Reavley & Jorm, 2014;Suh, Kim, & Byoun, 1995;Yoshioka, Reavley, Rossetto, & Nakane, 2016), and the results of which appear to differ according to the study population. For instance, studies have shown that relatives of patients with schizophrenia are more likely to believe that psychosocial factors are the main cause of schizophrenia than are biological or genetic factors (Magliano et al, 2001;Suh et al, 1995).Furthermore, a study on Korean laypeople revealed that they tend to endorse individual psychological causes such as internal conflict and a lack of will rather than socio-environmental, biological, or supernatural causes of schizophrenia (Lee & Suh, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the best available treatments appear to be antipsychotic medications (which is the first-line treatment) along with psychological and psychosocial treatments(U Khan, Martin-Montañez, & Chris Muly, 2013). Notably, a recent study conducted in Denmark showed that the general population has beliefs about the causes of schizophrenia that are in line with professional knowledge: namely, a hereditary explanation followed by improper upbringing and stressful life events (Jensen et al, 2016). However, most studies conducted in South Korea show that people tend to believe in individual psychological causes followed by social environmental causes and show a preference toward psychological counseling and therapy (Lee & Suh, 2010;Suh et al, 1995).…”
Section: Introductionmentioning
confidence: 99%